Driving Distance and Food Accessibility: A Geospatial Analysis of the Food Environment in the Navajo Nation and Border Towns - Bennion, Natalie; Redelfs, Alisha H.; Spruance, Lori; Benally, Shelby; Sloan-Aagard, Chantel (Frontiers in Nutrition, 2022)
The Navajo Nation experiences the highest rates of food insecurity in the U.S. and is classified as a food desert. The present study assessed the accessibility to food outlets (grocery stores, convenience stores, and restaurants) on the Navajo Nation and in selected surrounding border towns. This study aimed to visually represent driving time and food accessibility on and off the Navajo Nation. Food outlets located in neighboring border towns were examined using network analysis of driving distance to examine the spatial impact of driving time within the Navajo Nation. There were 14 grocery stores, 21 convenience stores, and 65 restaurants identified in the Navajo Nation as compared to border towns which had a total of 542 grocery stores, 762 convenience stores, and 3,329 restaurants equaling a ratio of about 50:1 (grocery, 39:1; convenience, 36:1; restaurants, 51:1) when comparing food outlets off versus on the Navajo Nation. This ecological study presents a visual representation of driving time and food accessibility, revealing geographic areas within the Navajo Nation where access to border town food stores is sparse, reducing their effectiveness as a supplement to increase access to healthy foods for Navajo Nation residents.